Atención de enfermería en caso probable de tetano neonatal - Mereci Fajardo, Karen Gissel; Iñiguez Martinez, Gloria Jazmin (Machala : Universidad Técnica de Machala, 2019)
Neonatal tetanus is a deadly disease caused by a Gram-positive bacterium Clostridium Tetani, which is introduced into the body by the umbilical cord, by not applying a asepsis and antisepsis technique in both the cut and the manipulation during The birth. Already admitted in the organism continues to the bloodstream and the central nervous system causing a hyperactivity of the motor neurons. International data mention that before immunizations neonatal tetanus was more frequent, according to estimates the World Health Organization in the year 2015 provoked the death of approximately 34.000 newborns however these data reflected a Significant decrease of 96% compared to the year 1988 that claimed the life of 787.000 newborns in their first 28 days of life. In the case of study is a female newborn of 4 days of birth; It is brought by mother to the obstetrical Hospital Ángela Loayza of Ollague to the area of emergency by presenting thermal increase of 37.5 ℃, more rejection to the suction, makes a food type vomit, Bradypnea, apneas of 5 to 10 seconds; Mother relates that at 2 days of life, family of newborn with the purpose of removing the clamp, it performs manipulation of the umbilical cord with sharp object (knife), then proceeds to burn umbilical cord with direct fire (candle) for two occasions. He enters the neonatology service presenting Icterus skin, prolonged capillary filling, respiratory distress 32-36 per minute, generalized muscular stiffness, bradypnea and trismus. It has continuous apneas, so we proceed to tracheal intubation remaining in mechanical ventilation SIMV mode. By clinical picture and by Mother's history with 5 prenatal controls and not remember vaccines, it is treated as suspected/confirmatory neonatal tetanus. So it starts with treatment with penicillin G sodium and metronidazole. Later, neonatal tetanus is ruled out and clinical Sepsis is diagnosed. The objective of this study is to analyse the probable case of neonatal tetanus in a term newborn; To develop a nursing care plan using Marjory Gordon's theory as a reference. The method used is qualitative, because it focuses on the collection of information and description of the clinical characteristics of the study population. The information was obtained through a bibliographical search in scientific articles, in manuals, guides of clinical practice and by the systematic review of the unique clinical history of the patient attended at the obstetric Hospital Ángela Loayza de Ollague. It was obtained as a result that the diagnosis of neonatal tetanus was ruled out because of the lack of evidence and the diagnosis of clinical sepsis was confirmed because the blood cultures performed were negative. It is concluded that it is essential to make an adequate assessment of the patient and to apply the differential diagnosis, in this way to determine a disease through the exclusion of other possible causes that have a clinical picture similar to the one that the patient presents. Marjory Gordon's theory allowed us to identify the altered patterns in the newborn in a systematized way. The nursing care process is essential in the professional practice of nursing, to carry out the interventions because it is oriented in the resolution of problems of the patient.
El tétano neonatal es una enfermedad mortal, provocada por una bacteria Gram positiva Clostridium tetani, que se introduce hacia el organismo mediante el cordón umbilical, al no aplicar una técnica de asepsia y antisepsia tanto en el corte como en la manipulación durante el nacimiento. Ingresado ya en el organismo continúa al torrente sanguíneo y al sistema nervioso central provocando una hiperactividad de las neuronas motoras. Datos internacionales mencionan que antes de las inmunizaciones el tétano neonatal era más frecuente, según estimaciones la Organización Mundial de la Salud en el año 2015 provocó la muerte de aproximadamente 34,000 recién nacidos sin embargo estos datos reflejaron una disminución significativa del 96% en comparación con el año 1988 que cobró la vida de 787,000 recién nacidos en sus primeros 28 días de vida. En el caso en estudio es un recién nacido de sexo femenino de 4 días de nacida; es traída por madre al Hospital Obstétrico Ángela Loayza de Ollague al área de emergencia por presentar alza térmica de 37,5 ℃, más rechazo a la succión, realiza un vómito tipo alimenticio, bradipnea, apneas de 5 a 10 segundos; madre refiere que a los 2 días de vida, familiar de neonato con la finalidad de retirar el clamp, realiza manipulación del cordón umbilical con objeto corto punzante (cuchillo), luego procede a quemar cordón umbilical con fuego directo (vela) por dos ocasiones. Ingresa al servicio de neonatología presentando piel ictérica, llenado capilar prolongado, dificultad respiratoria 32 - 36 por minuto, rigidez muscular generalizada, bradipnea y trismus. Presenta apneas continuas, por lo que se procede a intubación traqueal permaneciendo en ventilación mecánica modo SIMV. Por cuadro clínico y por antecedentes de madre con 5 controles prenatales y no recordar vacunas, se trata como tétano neonatal sospechoso/confirmatorio. Por lo que se inicia con tratamiento con Penicilina G Sódica y metronidazol. Posterior se descarta tétano neonatal y se diagnostica Sepsis clínica. El objetivo del presente estudio es analizar el caso probable de tétano neonatal en un recién nacido a término; para elaborar un plan de cuidados de enfermería utilizando como referencia la teoría de Marjory Gordon. El método utilizado es de tipo cualitativa, porque se centra en la recolección de información y descripción de las características clínicas de la población de estudio. La información se la obtuvo a través de una búsqueda bibliográfica en artículos científicos, en manuales, guías de práctica clínica y mediante la revisión sistemática de la historia clínica única de la paciente atendida en el Hospital Obstétrico Ángela Loayza de Ollague. Se obtuvo como resultado que se descartó el diagnóstico de tétano neonatal por la falta de evidencia y se confirmó diagnóstico de sepsis clínica debido a que los hemocultivos realizados fueron negativos. Se concluye que es esencial realizar una valoración adecuada del paciente y aplicar el diagnóstico diferencial, de esta manera determinar una enfermedad a través de la exclusión de otras posibles causas que tengan un cuadro clínico similar al que el paciente presenta. La teoría de Marjory Gordon nos permitió identificar de una manera sistematizada los patrones alterados en el recién nacido. El proceso de atención de enfermería es fundamental en la práctica profesional de Enfermería, para llevar a cabo las intervenciones ya que está orientado en la resolución de problemas del paciente.
Keywords: TEANO NEONATAL; CLOSTRIDIUM TETANI; SEPSIS NEONATAL; ATENCION DE ENFERMERIA